A Modified Third Harmonic Pulse-Width Modulation for Reduced Switching Loss in Cascaded H-Bridge Multilevel Inverters. Issue 4 (2019) - Kim, Seok-Min; Lee, Kyo-Beum
Abstract: A cascaded H-bridge multilevel inverter (CHMI) is one of the promising candidates for high-voltage direct current (HVDC) distribution system. The huge number of inverter cells and switching devices, which consists CHMI, imply a great switching loss and it requires increased cost and size of the cooling components. To reduce the huge switching loss, a pulse-width modulation (PWM) strategy is proposed in this paper, which is composed of two different modulation methods. In addition, an additional cell rotation method is proposed to evenly distribute power among inverter cells which allow shaping three-phase output currents with reduced switching loss. The simulation results verify the validity of the proposed modulation scheme.